The Politeness of Bungo Pasang Language Using Kato Nan Ampek in Minangkabau - Efrianto, Efrianto; Afnita, Afnita (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2019)
The purpose of this study was to describe the factors of politeness marker at expression of demand in the Minangkabau language in Bungo pasang area, Pesisir Selatan Regency of West Sumatra. Today the use of kato nan ampek in the expression of demand has begun to fade along with the times and technology. Linguistically, the expression of demand is reflected through (1) the length of speech, and (2) the use of non-imperative sentences. The object of this study was the Bungo Pasang community in the South Coastal District of 40-60 years who have a maximum junior high school education, with respondents who have the perfect utterance. The research method was descriptive qualitative that produces descriptive data in the form of written or verbal words from the respondents who were observed and interviewed. The results of this study are factors that determine politeness in demand; (a) implementation of performance, (2) variation of speech, and (3) completeness of speech. Then the politeness of demand in the Minangkabau language is manifested in (Lii) pragmatics and suprasegmental aspects, and kinesik. linguistic elegance is characterized by the use of the word help, and the use of the appropriate greeting.The purpose of this study was to describe the factors of politeness marker at expression of demand in the Minangkabau language in Bungo pasang area, Pesisir Selatan Regency of West Sumatra. Today the use of kato nan ampek in the expression of demand has begun to fade along with the times and technology. Linguistically, the expression of demand is reflected through (1) the length of speech, and (2) the use of non-imperative sentences. The object of this study was the Bungo Pasang community in the South Coastal District of 40-60 years who have a maximum junior high school education, with respondents who have the perfect utterance.The research method was descriptive qualitative that produces descriptive data in the form of written or verbal words from the respondents who were observed and interviewed. The results of this study are factors that determine politeness in demand; (a) implementation of performance, (2) variation of speech, and (3) completeness of speech. Then the politeness of demand in the Minangkabau language is manifested in (Lii) pragmatics and suprasegmental aspects, and kinesik. linguistic elegance is characterized by the use of the word help, and the use of the appropriate greeting